Evaluating ACT Processes in Relation to Outcome in Self-Help Treatment for Anxiety-Related Problems. Issue 6 (November 2020) - Ritzert, Timothy R.; Berghoff, Christopher R.; Tifft, Eric D.; Forsyth, John P.
Evaluating how, for whom, and under what conditions psychosocial treatments work is an important component of anxiety disorder treatment development. Yet, research regarding mediators and moderators of self-help interventions is sparse. The current project is a secondary analysis of mediators, moderators, and correlates of outcome of a randomized wait-list-controlled trial assessing acceptance and commitment therapy (ACT) self-help bibliotherapy for anxiety and related problems. Participants ( n = 503) were randomized to an immediate workbook ( n = 256) or wait-list condition ( n = 247). Nonparametric bootstrapped mediation analyses showed that pre–post positive changes in ACT treatment processes accounted for the relation between treatment and pre–post improvement on the primary outcomes of anxiety symptoms, depressive symptoms, and quality of life. Results indicated no baseline variables were significant moderators. Finally, hierarchical regression analyses indicated that the degree of improvement for each primary outcome was positively correlated with the degree to which participants reported applying the workbook material to their day-to-day life, over and above how much of the book they reported reading. This study provided support for the ACT model of change in a self-help context and highlighted the importance of actively applying self-help material, addressing theoretical and practical questions about how and why ACT self-help works.